Dorello's Canal and Gruber's Ligament: Historical Perspective - Ambekar, Sudheer; Sonig, Ashish; Nanda, Anil (Journal of Neurological Surgery Part B: Skull Base, 2012)
Wenzel Leopold Gruber and Primo Dorello were great anatomists and researchers during the 19th and 20th centuries. Their contributions to neuroanatomy—namely the Gruber's (petrosphenoidal) ligament and Dorello's canal, respectively—have come to be important structures in various approaches through the middle fossa. These structures have also helped provide us with an understanding of the mechanism of sixth nerve paresis in various pathological conditions, such as raised intracranial pressure and Gradenigo syndrome. Their numerous publications have stood as a reference to anatomical researchers. Gruber's description of internal mesogastric hernia and the Meckel-Gruber anastomosis are also widely known in medical literature. The following article is an attempt to reflect upon the life and works of Gruber and Dorello and the importance of their research.
Keywords: Dorello; Gruber; petrosphenoidal ligament; abducens nerve